Availability, Price and Affordability of Psychotropic Medicines in Addis Ababa, Ethiopia - Habte F; Shifa M; Berhanu H (Dove Medical Press, 2023)
Fikreselam Habte,1 Mekdes Shifa,2 Hana Berhanu2 1Department of Pharmacology and Clinical Pharmacy, School of Pharmacy, College of Health Science, Addis Ababa University, Addis Ababa, Ethiopia; 2Department of Pharmacy, Universal Medical and Business College, Addis Ababa, EthiopiaCorrespondence: Fikreselam Habte, Tel +251 913 39 40 44, Email habtefikreselam2007@gmail.com; fikreselam.habte@aau.edu.etBackground: Access to affordable, quality-assured essential medicines is crucial to reduce the burden of disease. However, one third of the world's population lacks regular access to essential medicines. The purpose of this study was to assess the availability, price, and affordability of medicines for mental disorders in Addis Ababa, Ethiopia.Methods: A cross-sectional study was done in selected pharmacies after modification of a WHO/HAI methodology developed questionnaire. Data on the availability and price of 28 lowest priced generics and originator brand essential psychotropic medicines were collected from seven public sectors, five private sectors, and seven other sectors (five Kenema Public Community Pharmacies and two Red Cross Pharmacies) in Addis Ababa between May 9 and May 31, 2022. The data were analyzed using the developed WHO/HAI workbook part I Excel sheet. Descriptive results were reported in text and table format.Results: The overall availability of lowest-priced generics medication was 41.69%. The availability of lowest-priced generics and originator brand medication was 54.68% and 1.7% in the public pharmacies; 24.14% and 0.0% in private pharmacies; 43% and 0.0% in Red Cross Pharmacies; and 42% and 3.2% in Kenema Public Community Pharmacies. The median price ratio in the public, private, Red Cross, and Kenema Public Community pharmacies was 1.26, 3.72, 1.65, and 1.59, respectively. Most of the medications were unaffordable. A patient could be required to pay up to 73 days wages to purchase a standard treatment for 1 month.Conclusion: The availability of psychotropic medicines was lower than the WHO target for non-communicable diseases and most of the available medicines were unaffordable.Keywords: access to medicine, low income country, mental disorder, Ethiopia